Nocturnal Enuresis in Children: A Literature Review of Pathophysiology, Diagnosis, and Management - Szczerek, Emilia; Płóciniczak, Viktoria (Quality in Sport, 2025)
Background: Nocturnal enuresis (NE), or bedwetting, is a highly prevalent chronic condition affecting up to 24% of the pediatric population. Despite its commonality, NE carries a significant psychosocial burden, negatively impacting a child’s self-esteem and quality of life. The condition’s etiology is complex and multifactorial, involving nocturnal polyuria, reduced bladder capacity, and impaired arousal mechanisms. Aim: This comprehensive review analyzes the evidence from various studies evaluating the current understanding of pathophysiology, diagnostic classification, and evidence-based management strategies for nocturnal enuresis in children. Materials and Methods: The review included scientific papers sourced from the PubMed and Google Scholar databases. Results: The literature review confirms the multifactorial etiology of nocturnal enuresis, including strong genetic predisposition, reduced nocturnal bladder capacity, and an association with upper airway obstruction. Key treatment methods include the enuresis alarm and desmopressin, with the lyophilisate. Desmopressin is generally safe when fluid restrictions are maintained. NE significantly negatively impacts the child’s quality of life and places a psychological burden on caregivers. Conclusions: Nocturnal enuresis is a common and complex condition with inconsistent diagnostic criteria and a multifactorial etiology. Effective treatment requires a combined approach of non-pharmacological methods (with the enuresis alarm as first-line therapy) and pharmacological methods (led by desmopressin), while second and third-line drugs carry greater risks. Due to the significant negative impact of NE on the quality of life of patients and their families, empathetic care and education are crucial. Further research is necessary to standardize therapeutic protocols and evaluate new interventions, such as vitamin supplementation.